The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1158/1535-7163.mct-10-0581
|View full text |Cite
|
Sign up to set email alerts
|

A Small-Molecule Inhibitor of MDMX Activates p53 and Induces Apoptosis

Abstract: The p53 inactivation caused by aberrant expression of its major regulators (e.g., MDM2 and MDMX) contributes to the genesis of a large number of human cancers. Recent studies have shown that restoration of p53 activity by counteracting p53 repressors is a promising anticancer strategy. Although agents (e.g., nutlin3a) that disrupt MDM2-p53 interaction can inhibit tumor growth, they are less effective in cancer cells that express high levels of MDMX. MDMX binds to p53 and can repress the tumor suppressor functi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(111 citation statements)
references
References 52 publications
3
105
0
1
Order By: Relevance
“…The role of inactivation of wild-type p53 resulting from up-regulation of MDM2 (and/or MDM4) has recently been explored. [28][29][30][31]42,43 Our data confirmed that MDM2 protein levels are higher to various degrees in PV CD34 ϩ cells than that in normal CD34 ϩ cells. Additional studies will be required to determine whether MDM2 levels can be used to predict in vitro or in vivo responses to IFN-␣ and nutlin treatment.…”
Section: Discussionsupporting
confidence: 63%
“…The role of inactivation of wild-type p53 resulting from up-regulation of MDM2 (and/or MDM4) has recently been explored. [28][29][30][31]42,43 Our data confirmed that MDM2 protein levels are higher to various degrees in PV CD34 ϩ cells than that in normal CD34 ϩ cells. Additional studies will be required to determine whether MDM2 levels can be used to predict in vitro or in vivo responses to IFN-␣ and nutlin treatment.…”
Section: Discussionsupporting
confidence: 63%
“…Agents suppressing the interaction of p53 with these E3 ligases result in accumulation of p53, triggering apoptotic cancer cell death, making them prime drug design candidates (34). Many compounds, including serdemetan, nutlin-3 (RO5045337), and NSC-207895 all demonstrate in vitro anticancer activity (35)(36)(37). Serdemetan was tested in a phase I trial, with p53 induction seen, but cardiac conduction defects were observed (38).…”
Section: Therapeuticsmentioning
confidence: 99%
“…XI-100 blocks MdmX transcription and acts synergistically with nutlin in cancer cell lines overexpressing MdmX [44].…”
Section: Targeting Mdmxmentioning
confidence: 99%